Poverty, inequality and social policies in Brazil, 1995-2009 - Pedro H. G. Ferreira de Souza (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
Since the mid-1990s, Brazil has undergone extensive reforms that have finally reversed the dismaying economic performance of the 1980s. In particular, poverty and inequality indicators have improved dramatically, especially since the late-2000s. This paper provides an overview of such recent trends and discusses the role played by four major government interventions: public education, the minimum wage law, Social Security pensions and Social Assistance transfers. Additionally, available data sets and methods for policy evaluation are also discussed.
Keywords: 330; Armut; Einkommensverteilung; Sozialpolitik; Brasilien